Pengelolaan Perpustakaan Digital dalam Meningkatkan Literasi Siswa Kelas 7 - Sri Uswatun Hasanah (Lembaga Pengembangan Kinerja Dosen, 2025)
Advancements in information technology have brought significant changes to the field of education, particularly in the ways students access and utilize information. One important innovation in this area is the development of digital libraries in schools. Digital libraries not only serve as repositories for electronic reading materials but also function as essential instruments for fostering information literacy and a reading culture among students. This study aims to analyze how digital library management can enhance the literacy of seventh-grade students in junior high schools. The method used is descriptive qualitative with a literature study approach, referring to six nationally and internationally indexed scientific articles. The findings indicate that the success of digital library management is strongly influenced by the principal’s leadership, the competencies of teachers and librarians, the readiness of technological infrastructure, and the quality of services provided. Principals who apply transformational leadership styles are proven to effectively promote a culture of digital literacy within the school. Digitally competent teachers and librarians play a crucial role in guiding students to use information sources wisely. In addition, interactive and easily accessible digital library services increase reading interest and information literacy skills among seventh-grade students. This study underscores the importance of digital library management that is not only technology-oriented but also emphasizes leadership, collaboration, and the empowerment of human resources within the school environment.